2010
DOI: 10.1016/j.jmarsys.2010.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Surface CO2 parameters and air–sea CO2 flux distribution in the eastern equatorial Atlantic Ocean

Abstract: Toute ma gratitude au Professeur Georges KOUADIO, mon directeur de thèse, qui a conduit mes premiers pas dans la recherche depuis le DEA jusqu'à la thèse.Je remercie les Directeurs de recherche Jacqueline BOUTIN et Nathalie LEFEVRE de m'avoir accueilli si gentiment au LOCEAN et pour m'avoir encadré et aidé sans relâche à surmonter mes difficultés, pendant cette thèse en cotutelle. Je leur dit un grand merci pour leur disponibilité à répondre à toutes mes questions et leurs remarques pour l'amélioration de ce d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 39 publications
6
28
1
Order By: Relevance
“…Hence, the parameterization of C T includes both physical (S and T ) and/or biological parameters (Bakker et The results of the 10-fold cross-validation analysis showed that a first-order polynome fits C T to S and T with an RMSE of 16.25 µmol kg −1 and r 2 = 0.87. These values are comparable to the RMSE and r 2 found by previous empirical approaches applied in the eastern Atlantic (Bakker et al, 1999;Koffi et al, 2010). However, we found that a third-order polynome improved the RMSE and r 2 of the equation compared to the first-order fit (Eq.…”
Section: Fitting C T In the Mediterranean Sea Surface Waterssupporting
confidence: 89%
“…Hence, the parameterization of C T includes both physical (S and T ) and/or biological parameters (Bakker et The results of the 10-fold cross-validation analysis showed that a first-order polynome fits C T to S and T with an RMSE of 16.25 µmol kg −1 and r 2 = 0.87. These values are comparable to the RMSE and r 2 found by previous empirical approaches applied in the eastern Atlantic (Bakker et al, 1999;Koffi et al, 2010). However, we found that a third-order polynome improved the RMSE and r 2 of the equation compared to the first-order fit (Eq.…”
Section: Fitting C T In the Mediterranean Sea Surface Waterssupporting
confidence: 89%
“…According to Koffi et al (2010); Lefèvre et al (2010), and Bonou et al (2016) in the WTNA, SSS has been shown to be highly correlated with TA and DIC.…”
Section: Discussionmentioning
confidence: 95%
“…Using the SSS recorded at the mooring with the highest available resolution (hourly in 2006 and 2007; daily in 2008 and 2009), TA was calculated with the relationship determined by Koffi et al (2010). The standard error on the predicted alkalinity is ±7.2 μmol kg −1 .…”
Section: Methodsmentioning
confidence: 99%